Endoplasmic reticulum stress-related features predict the prognosis of osteosarcoma and reveal STC2 as a novel risk indicator for disease progression - Yu, Yongle; Yu, Jiadong; Pan, Zhenyu (Frontiers in Oncology, 2024)
Endoplasmic reticulum (ER) stress exerts significant effects on cell growth, proliferation, migration, invasion, chemoresistance, and angiogenesis in various cancers. However, the impact of ER stress on the outcomes of osteosarcoma patients remains unclear. In this study, we established an ER stress risk model based on The Cancer Genome Atlas (TARGET) osteosarcoma dataset to reflect immune features and predict the prognosis of osteosarcoma patients. Survival analysis revealed significant differences in overall survival among osteosarcoma patients with different ER stress-related risk scores. Furthermore, ER stress-related risk features were significantly associated with the clinical pathological characteristics of osteosarcoma patients and could serve as independent prognostic indicators. Functional enrichment analysis indicated associations of the risk model with cell chemotaxis, leukocyte migration, and regulation of leukocyte migration. Additionally, the ER stress-related risk model suggested the presence of an immunosuppressive microenvironment and immune checkpoint responses. We validated the significance of 7 ER stress-related genes obtained from LASSO regression analysis through RT-qPCR testing on osteosarcoma samples from a local hospital, and inferred the importance of STC2 based on the literature. Subsequently, IHC experiments using samples from 70 osteosarcoma cases and 21 adjacent tissue samples confirmed differential expression of STC2 between cancer and normal tissues, and explored the gene’s expression in pan-cancer and its association with clinical pathological parameters of osteosarcoma. In conclusion, we have proposed an ER stress risk model as an independent prognostic factor and identified STC2 as a novel risk indicator for disease progression, providing a promising direction for further research and treatment of osteosarcoma.